2022
DOI: 10.3390/ijms232112710
|View full text |Cite
|
Sign up to set email alerts
|

Specificities of the DMD Gene Mutation Spectrum in Russian Patients

Abstract: Duchenne/Becker muscular dystrophy (DMD/BMD) is the most common form of muscular dystrophy, accounting for over 50% of all cases. In this regard, in Russia we carry out a program of selective screening for DMD/BMD, which mainly involves male patients. The main inclusion criteria are an increase in the level of creatine phosphokinase (>2000 U/L) or an established clinical diagnosis. At the first stage of screening, patients are scanned for extended deletions and duplications in the DMD gene using multiplex l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…20 One Russian study showed spectrum of dystrophin gene mutation that revealed 49% gross deletion, 14.5% duplications and 36.5% minor mutations and among which 19.3% turned out to be nonsense mutations. 21 Identification of this nonsense mutation is important for the therapeutic usage of read through medicines. Mutational analysis among 68 families of Kuwait revealed 66% deletion, 4.4% duplications and 5.8% nonsense mutations.…”
Section: Discussionmentioning
confidence: 99%
“…20 One Russian study showed spectrum of dystrophin gene mutation that revealed 49% gross deletion, 14.5% duplications and 36.5% minor mutations and among which 19.3% turned out to be nonsense mutations. 21 Identification of this nonsense mutation is important for the therapeutic usage of read through medicines. Mutational analysis among 68 families of Kuwait revealed 66% deletion, 4.4% duplications and 5.8% nonsense mutations.…”
Section: Discussionmentioning
confidence: 99%